2021
DOI: 10.3390/biology10030191
|View full text |Cite
|
Sign up to set email alerts
|

Biodiscovery of Potential Antibacterial Diagnostic Metabolites from the Endolichenic Fungus Xylaria venustula Using LC–MS-Based Metabolomics

Abstract: Three species of the lichen Usnea (U. baileyi (Stirt.) Zahlbr., U. bismolliuscula Zahlbr. and U. pectinata Stirt.) and nine associated endolichenic fungi (ELF) were evaluated using a metabolomics approach. All investigated lichen crude extracts afforded antibacterial activity against Staphylococcus aureus (minimum inhibitory concentration (MIC): 0.0625 mg/mL), but none was observed against Escherichia coli, while the ELF extract Xylaria venustula was found to be the most active against S. aureus (MIC: 2.5 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Among all the evaluated strains, D. endophytica exhibited a color transition during the fermentation time, which corresponded to its ECE's potent bioactivity, resulting in an organic extract with the highest potential obtained during the primary screening. In addition, even when the evaluated mycelial organic crude extracts were found bioactive only against the Gram-positive pathogen, it is noting that the obtained extraction yields are within the range of obtained values for the solid fermentation of endolichenic fungi on rice media, where also Xylariaceae species presented the highest extraction yields (Santiago et al, 2021).…”
Section: Primary Screeningsupporting
confidence: 63%
See 1 more Smart Citation
“…Among all the evaluated strains, D. endophytica exhibited a color transition during the fermentation time, which corresponded to its ECE's potent bioactivity, resulting in an organic extract with the highest potential obtained during the primary screening. In addition, even when the evaluated mycelial organic crude extracts were found bioactive only against the Gram-positive pathogen, it is noting that the obtained extraction yields are within the range of obtained values for the solid fermentation of endolichenic fungi on rice media, where also Xylariaceae species presented the highest extraction yields (Santiago et al, 2021).…”
Section: Primary Screeningsupporting
confidence: 63%
“…The presented study also emphasizes on the crucial role of systematical screening platforms in the rapid and effective prioritization of antimicrobial agents prior to chemical investigation of bioactive molecules. In some cases, the cost and investing time associated to the identification of new antimicrobial compounds could be avoid by the screening of microorganisms, which are previously known to produce specific potential antimicrobial agents into crude extracts (Caicedo et al, 2011;Santiago et al, 2021). Nonetheless, our results provide an initial step toward bioprospecting the Colombian southwestern endophyte diversity and highlight the value of preserving the native habitats owing to their promising ecosystemic applications in the biotechnological and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 88%
“…It is, thus, possible that ELF protects the host against harmful conditions through the production of reactive oxygen species (ROS). Furthermore, Santiago and colleagues [37] recently reported that ELF metabolites may have protected the lichen from other possible harmful or invading microorganisms. Such assumption resulted from the metabolomics analyses of lichen hosts and their associated ELF, where a distinction between lichen and ELF metabolic profiles was observed.…”
Section: Endolichenic Fungi (Elf) and Their Role In The Lichen Symbiosismentioning
confidence: 99%
“…In particular, enormous progress in LC-MS-based metabolomics has been made, providing researchers with a variety of chromatographic separation, ionization, and mass analysers [38,39]. Moreover, it has also been applied in the dereplication of already known substances in the early stages of the screening process of bioactive mixtures [40][41][42].…”
Section: Introductionmentioning
confidence: 99%